ANALISIS KELAYAKAN MEDIA PEMBELAJARAN HERBARIUM DALAM MENINGKATKAN KEMAMPUAN KREATIVITAS SISWA PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Pujiasti, Dea Asri; Dewi, Citra Kusuma; Muslihah, Neni Nadiroti (IPI Press, 2021)
In today’s information age, the ability for creativity is one of the competencies that every student must have. However, science learning in elementary schools has not provided many opportunities for students to develop this ability. Therefore, it is necessary to make efforts to improve students' creative abilities, one of which is by using herbarium learning media. The purpose of this study was to analyze the feasibility of herbarium learning media in increasing students' creativity in science learning in elementary schools. The method used in this research is descriptive qualitative. The research instrument consisted of a questionnaire, observation sheets, and interviews. The results of the questionnaire data processing show that the creativity of students when seen in general in science learning using herbarium learning media, as well as from each indicator, and the attitude scale of each individual shows creative interpretation with 70% of students getting the creative category and 30% of students getting the very category creative. Overall, the quality of herbarium learning media is very suitable to be used to support learning in increasing student creativity in science learning in elementary schools.